ANALISIS STRATEGI DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN DI PUSAT OLEH-OLEH DBFOODS PADANG - Putra, Ridho Mardi; Asnur, Lise (Komunitas Manajemen Kompetitif, 2024)
This research is supported by researchers' observations on Analisis Digital Marketing dalam meningkatkan Penjualan di Pusat Oleh-Oleh Dbfoods Padang. This digital marketing can be described by reviewing and meeting STP indicators (Segmentation, Targeting, Positioning), Marketing Mix. as well as assisted with SWOT Analysis. This type of research is descriptive research with qualitative data. Data collection techniques are done by observation methods, interviews, and documentation. Determination of research informants using purposive sampling techniques consists of Director and Operational Manager, Production Manager, Marketing Manager and Administration Center by Dbfoods Field. Data analysis techniques performed are data collection, data reduction, data presentation, and conclusion making. The results of the research concluded that the Digital Marketing Strategy in helping sales in the Dbfoods Field Center is: DbFoods chooses demographic segmentation groups and consumer attitudes in digital marketing activities, target markets are young and active families using the Internet, Positioning Dbfoods is oriented to become a bridge connecting communication to the target market by describing the identity and quality of the product. Dbfoods uses shopee marketplaces, social media Instagram and Whatsapp in their digital marketing activities